Efficacy and safety of abaloparatide, denosumab, teriparatide, oral bisphosphonates, and intravenous bisphosphonates in the treatment of male osteoporosis: a systematic review and Bayesian network meta-analysis - Chen, Liangshi; Ji, Bomei; Xia, Cong (Frontiers in Endocrinology, 2025)
Study DesignA Systematic Review and Bayesian Network Meta-AnalysisObjectiveTo compare the efficacy and safety of abaloparatide (ABA), denosumab (DEN), teriparatide (TER), oral bisphosphonates (OBP), and intravenous bisphosphonates (IBP) in the treatment of male osteoporosis through a network meta-analysis.Summary of Background DataCurrently, a variety of medications are available for the treatment of male osteoporosis, including abaloparatide, denosumab, teriparatide, and bisphosphonates. These medications are widely applied in male osteoporosis, and existing randomized controlled trials (RCTs) provide strong evidence of their efficacy. However, there is a lack of sufficient systematic comparative studies to guide the choice between these treatments, particularly for specific male osteoporosis populations.MethodsThis systematic review and network meta-analysis (NMA) were conducted strictly in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and the relevant standards recommended by the Cochrane Collaboration. We performed pairwise meta-analysis using Stata 18.0 software to assess the magnitude of effect sizes and the consistency of findings across studies. For network meta-analysis (NMA), we used R version 4.3.1 along with the gemtc and BUGSnet packages to handle complex multi-treatment comparisons. Using these methods, we were able to comprehensively assess the relative efficacy and safety of different treatment options. All statistical analyses were conducted using Review Manager software (version 5.4), a widely used tool in medical research for meta-analysis, forest plot generation, and bias risk assessment.ResultsOverall, clinical decisions should carefully balance drug efficacy and safety. Although TER performs best in reducing the occurrence of all adverse events, its efficacy in some BMD targets (such as total hip BMD) is relatively lower. In comparison, while OBP has a clear advantage in reducing severe adverse events, its efficacy in some BMD improvements (such as femoral neck BMD) is slightly less. Therefore, clinicians should consider the specific needs of the patient, the treatment goals, and the safety profile of the drug when selecting a medication, particularly for long-term use.ConclusionThe results indicate that abaloparatide and teriparatide are significantly superior to other drugs in improving lumbar spine and femoral neck BMD, while oral bisphosphonates is the most effective in improving total hip BMD. In terms of safety, teriparatide demonstrates the best performance in all adverse events, and oral bisphosphonates shows a clear advantage in reducing severe adverse events. Future treatment decisions should balance efficacy and safety, with clinical treatment tailored to the individual needs of the patient, including the site of bone loss and sensitivity to adverse events. Future research should explore combination therapies or multi-target strategies to optimize both efficacy and safety.